Clinical and laboratory markers associated with anti-TNF-alpha trough levels and anti-drug antibodies in patients with inflammatory bowel diseases. Issue 10 (March 2020) - Grinman, Ana B.; de Souza, Maria das Graças C.; Bouskela, Eliete; Carvalho, Ana Teresa P.; de Souza, Heitor S. P.
Abstract : Abstract: Monitoring anti-TNF agents in inflammatory bowel disease (IBD) patients may be helpful in optimizing outcomes. We aimed to evaluate potential correlations among demographic, clinical, laboratory, or imaging parameters, as well as serum levels of infliximab (IFX) and adalimumab (ADA) and their respective antibodies, in the clinical management of IBD patients. A cross-sectional study of 95 patients with Crohn's disease (CD) or ulcerative colitis (UC) in maintenance therapy with infliximab or adalimumab was performed. Drug trough levels and anti-drug levels were determined using ELISA-based assays. Regarding the serum IFX dosage, patients with higher relative C-reactive protein (CRP) levels had significantly lower relative serum IFX levels (<3 μg/mL) ( P = .028). In contrast, higher concentrations of anti-IFX antibodies were found in patients who were not on concomitant immunomodulators ( P = .022) and who had more biological-related adverse events ( P = .001) and higher levels of CRP ( P = .042). Serum CRP levels were also negatively correlated with IFX (CC = −0.315; P = .033) but positively correlated with the presence of IFX antibodies (CC = 0.327; P = .027). Serum albumin dosage showed a positive correlation with levels of both IFX (CC = 0.379; P = .004) and ADA (CC = 0.699; P = .003). Although anti-TNF-α trough levels and immunogenicity do not show a significant correlation with disease outcome, our results reinforce the use of combination therapy for patients treated with infliximab. Moreover, we confirmed the presence of significant associations between anti-TNF-α trough levels and immunogenicity with body mass index (BMI), the concomitant use of immunomodulators, the rates of side effects, and laboratory markers, including serum albumin and CRP.